Brief Report: HIV Drug Resistance in Adults Failing Early Antiretroviral Treatment. (1st July 2016) - Fogel, Jessica M.; Hudelson, Sarah E.; Ou, San-San; Hart, Stephen; Wallis, Carole; Morgado, Mariza G.; Saravanan, Shanmugam; Tripathy, Srikanth; Hovind, Laura; Piwowar-Manning, Estelle; Sabin, Devin; McCauley, Marybeth; et al.
Abstract : Abstract: Early initiation of antiretroviral treatment (ART) reduces HIV transmission and has health benefits. HIV drug resistance can limit treatment options and compromise use of ART for HIV prevention. We evaluated drug resistance in 85 participants in the HIV Prevention Trials Network 052 trial who started ART at CD4 counts of 350–550 cells per cubic millimeter and failed ART by May 2011; 8.2% had baseline resistance and 35.3% had resistance at ART failure. High baseline viral load and less education were associated with emergence of resistance at ART failure. Resistance at ART failure was observed in 7 of 8 (87.5%) participants who started ART at lower CD4 cell counts.